1999
DOI: 10.1542/peds.103.4.e49
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Newborn Infants Have a High Plasma Creatinine?

Abstract: The riddle of the high Pcr levels in term and particularly in preterm newborns seems to be solved. Once the umbilical cord is severed, the perfect intrauterine maternal-fetal biochemical balance is disturbed. Thereafter, the already transferred exogenous, adult-level creatinine will rapidly disappear in the first urine specimens passed by the now autonomous newborn infant. A new steady state is achieved in due time, based on independent neonatal factors. One of these factors is the unusual occurrence of tubula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
157
0
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(177 citation statements)
references
References 5 publications
14
157
0
6
Order By: Relevance
“…After birth, SeCr increases in the first 48 h in preterm infants. 7,8 Consistent with these data, our results showed that the main factors analyzed found to be related to baseline SeCr were HDP, a condition that is often associated with high maternal levels of SeCr, and advancing hour of life. Placental abruption and GA explained only a very small proportion of the variability of the first day neonatal SeCr in our study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…After birth, SeCr increases in the first 48 h in preterm infants. 7,8 Consistent with these data, our results showed that the main factors analyzed found to be related to baseline SeCr were HDP, a condition that is often associated with high maternal levels of SeCr, and advancing hour of life. Placental abruption and GA explained only a very small proportion of the variability of the first day neonatal SeCr in our study.…”
Section: Discussionsupporting
confidence: 88%
“…In preterm infants born less than 32 weeks of gestational age (GA), previous reports showed that SeCr concentration had a postnatal increase with a peak between the second and the fourth day of life that was followed by a SeCr decrease. 5 Both the increased peak and the slow decrease of SeCr in smaller premies reflect decreased renal function associated with low GA. 6 Postnatal SeCr changes in preterm infants may result from tubular creatinine reabsorption in the immature kidney 7 and from a physiologically low GFR during the first days of life. 8 Moreover, in sick preterm infants, many clinical conditions inducing hypotension, hypovolemia and hypoxemia and the use of nephrotoxic drugs may lead to further reduction of GFR.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] While in the immediate postnatal period the newborn SCr likely reflect maternal values, 2,4 further increase in the levels of SCr in premature infants have been attributed to increased tubular reabsorption of creatinine due to renal tubular immaturity and also to reduced creatinine clearance. 2,3 It has also been shown by several investigators that creatinine clearance and glomerular filtration rate (GFR) increase with postnatal age in premature infants, [5][6][7][8] and in the absence of urine creatinine measurements, SCr can be used to estimate GFR. [9][10][11][12] However, little is known about the relationship between gestational age/birth weight (GA/BW) and SCr in VLBW infants at birth following stabilization of their SCr.…”
Section: Introductionmentioning
confidence: 99%
“…The authors hypothesize that this latter temporary phenomenon is attributable to back flow of creatinine across leaky immature tubular and vascular structures. With time, maturational renal changes will impose a barrier to creatinine [2]. Secondly by suggesting that there is scanty Indian literature on the subject of renal functions in neonates, are the authors contemplating difference in different racial groups?…”
mentioning
confidence: 99%
“…The study is descriptive presentation of facts as observed in subgroups of neonates classified as per gestational age. Pointing out this to be a methodological error in the study is notjustifieable and unwanted because various other authors [2,3] showed renal functional maturation is gestational age dependent adaptation in neonatology of the once daily concept of aminoglycoside administration has been well studied. Langhendries JP et al [4] have been able to demonstrate after a trial period of single dose amikacin in 37 babies that minimum inhibitory concentration profiles tested in 43 successive bacterial, strains remained adequate.…”
mentioning
confidence: 99%